Capital and Technical Assistance Needs of Georgia's Health-Related Nonprofits: An Exploratory Study - Jerry Daniel; Cherysh Green-Caldwell (Georgia Southern University, 2016)
Background: Nonprofit organizations, particularly those related to health and human services, are involved in addressing needs of the American population. They provide an array of services in small and large communities throughout the United States. Compared to for-profit organizations, health-related nonprofits are increasing in number. Despite having a substantial share of the health care market, nonprofit organizations face difficulties delivering services to those in need. The difficulties faced by rural nonprofits may be greater than those for their urban counterparts. The impetus for this study came from Healthcare Georgia Foundation's goal of strengthening nonprofits to address the burgeoning health inequities in Georgia. The purpose was to gain a better understanding of the capital and technical assistance needs of health-related nonprofits. The specific aim was to answer a set of exploratory questions. Methods: This study utilized exploratory, descriptive methodology to examine the capital and technical assistance needs of health-related nonprofits in the state of Georgia. Organizational management staff was used as the unit of analysis. A crosssectional, correlational design was used to gauge participants' views about their organization's current needs. The sample consisted of 48 rural and 45 urban/metropolitan nonprofits. Results: The findings provide information related to the capital and technical assistance needs of rural and urban healthrelated nonprofits in Georgia and reveal specific needs of nonprofits focusing on health and social services. Conclusions: The results have public health implications for a state that currently faces various public health challenges. Nonprofits located in rural areas could use more technical assistance in reaching their funding goals.